Control Charts Usage for Monitoring Performance in Surgery: A Systematic Review. Issue 2 (6th March 2023) - Le Thien, My-Anh; Cordier, Quentin; Lifante, Jean-Christophe; Carty, Matthew J.; Duclos, Antoine
Abstract : Objectives: The control chart is a graphical tool for data interpretation that detects aberrant variations in specific metrics, ideally leading to the identification of special causes that can be resolved. A clear assessment of control chart utilization and its potential impact in surgery is required to justify recommendations for its dissemination. This review aims to describe how performance monitoring using control charts was used over time in surgery. Methods: A systematic search of PubMed regarding statistical process control in surgery from its inception until December 2019 was performed using Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Information extracted from selected publications included study aim and population setting, monitored indicators, control charts methodological parameters, and implementation strategy. Results: One hundred thirteen studies met the selection criteria with a median of 1916 monitored patients. Overall, 57.5% of studies focused on control chart methodology, 24.8% aimed at evaluating performance changes using control charts retrospectively, and 17.7% implemented control charts for continuous quality improvement prospectively. Although there was a great diversity of used indicators and charting tools, the evaluation of patient safety (72.6%) or efficiency (15.9%) metrics based on Shewhart control chart (33.6%) or cumulative sum chart (54.9%) were common. To foster control charts implementation, 14 studies promoted their periodic review, but only three assessed their impact on patient outcomes. Conclusions: The scientific literature supports the feasibility and utility of control chart to improve patient safety in multiple surgical settings. Additional studies are necessary to reveal the optimal manner in which to implement this affordable tool in surgical practice.